Rapid identification of differentially expressed genes in trypanosomes - Murphy, N.B.; Pelle, Roger (Springer, 1997)
Members of the genus Trypanosoma, within the order Kinetoplastida, are unicellular parasitic organisms which are a major threat to human health and livestock productivity in large areas of the developing world. Despite their relatively small genome size, these primitive organisms undergo complex life cycles, are capable of controlling their rates of proliferation at different stages, can modulate the immune system of their mammalian hosts, and, more recently, have been shown to undergo programmed cell death (see Ameisen et al. 1995; Vickerman 1985; Zilberstein and Shapira 1994). Many of the molecular features and processes of these organisms provide paradigms for eukaryotic biology (see Adler and Hajduk 1994; Bonen 1993; Gonners-Ampt and Borst 1995; Pays et al. 1994; Simpson and Maslov 1994; Tschudi and Ullu 1994). To gain a better understanding of the molecular mechanisms involved in the control of differentiation of these intriguing and deadly organisms we have developed a differential display PCR method, dubbed randomly amplified differentially expressed sequences (RADES), for the rapid identification of differentially expressed trypanosome or leishmania genes (Murphy and Pelle 1994).